Effects of mouthwashes on Knoop hardness and surface roughness of dental composites after different immersion times - Diogo de Azevedo Miranda; Carlos Eduardo dos Santos Bertoldo; Flávio Henrique Baggio Aguiar; Débora Alves Nunes Leite Lima; José Roberto Lovadino (Sociedade Brasileira de Pesquisa Odontológica, 2011)
The aim of this in vitro study was to evaluate the effect of different mouthwashes on superficial roughness and Knoop hardness of two resin composites. Eighty specimens (6 mm Ø and 2 mm height) were prepared and divided into eight experimental groups (n = 10) according to the resin composites (4 Seasons and Esthet X), and storage solutions (G1 - Distilled water; G2 - Colgate Plax Overnight; G3 - Colgate Plax Alcohol Free; and G4 - Colgate Plax Whitening). The initial hardness and roughness readings (T1) were measured and then the specimens were stored in 2 mL of mouthwash for 12 h (T2) and 24 h (T3). The data were analyzed with repeat-measures two-way ANOVA and Tukey's test (α = 5%). Regardless of the type of solution and time of exposure, there was no statistical difference for roughness between the resins (p = 0.44). G4 and G8 presented higher roughness means than G1, G3, G5 and G7, after 12 and 24 hours of immersion. For Knoop microhardness analysis, there was a significant reduction for all groups after 12 hours and 24 hours. We conclude that the mouthwashes containing hydrogen peroxide and/or alcohol decrease the microhardness of the resins tested; however, the mouthwash containing hydrogen peroxide had a higher deleterious effect on roughness.